2017
DOI: 10.1051/0004-6361/201730550
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundances of two extragalactic young massive clusters

Abstract: Aims. We use integrated-light spectroscopic observations to measure metallicities and chemical abundances for two extragalactic young massive star clusters (NGC1313-379 and NGC1705-1). The spectra were obtained with the X-Shooter spectrograph on the ESO Very Large Telescope. Methods. We compute synthetic integrated-light spectra, based on colour-magnitude diagrams for the brightest stars in the clusters from Hubble Space Telescope photometry and theoretical isochrones. Furthermore, we test the uncertainties ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(77 citation statements)
references
References 106 publications
5
72
0
Order By: Relevance
“…The stellar metallicities necessary to constrain the relationship between massive star iron abundances and gas-phase oxygen require expensive space telescope UV observations or deep near-infrared data if red supergiants are present, and thus only a handful of quantitative measurements independent of the gas-phase exist in unresolved local galaxies (e.g. Larsen et al 2008;Lardo et al 2015;Hernandez et al 2017Hernandez et al , 2019Chisholm et al 2019).…”
Section: Abundances In Extreme Nearby Star-forming Galaxies and The S...mentioning
confidence: 99%
“…The stellar metallicities necessary to constrain the relationship between massive star iron abundances and gas-phase oxygen require expensive space telescope UV observations or deep near-infrared data if red supergiants are present, and thus only a handful of quantitative measurements independent of the gas-phase exist in unresolved local galaxies (e.g. Larsen et al 2008;Lardo et al 2015;Hernandez et al 2017Hernandez et al , 2019Chisholm et al 2019).…”
Section: Abundances In Extreme Nearby Star-forming Galaxies and The S...mentioning
confidence: 99%
“…We create a grid of stellar models accounting for stellar rotation of ∼200 km s −1 , spanning metallicities of 0.001 < Z < 2 and temperatures of 32,500 <T(K)< 55,000. For each target we select only those models that have the same stellar metallicity as their nebular gas (several studies have shown this to be an accurate assumption, see Hernandez et al 2017;Chisholm et al 2019) but different effective temperature. We focus the fitting procedure on the C III λ1175 line, minimizing χ 2 between the rest wavelength range of 1160-1185 Å.…”
Section: Photoionization Modelingmentioning
confidence: 99%
“…Although several recently developed full-spectrum fitting techniques do not directly fit for extinction (e.g., Chilingarian et al 2007;Larsen et al 2012;Hernandez et al 2017), it is important to note that age and extinction do affect the shape of spectra in a similar way, especially when the spectral range does not include a strong break such as the Balmer jump.…”
Section: The Role Of Extinctionmentioning
confidence: 99%